مکرراتِ قرآن اور امام بقاعیؒ - ڈاکٹر حبیب اللہ چشتی (FIKR-O NAZAR فکر ونظر, 2013)
Mukarrarat-ul-Quran means the repetition of any ayah or story in the Quran. Imam Biqai, in hiscommentary Nazm al-durar fi tanasub al ayat wa-’l-suwar, is of the view that such repetition is not repugnant to the eloquence of Quran, rather it adds to its beauty and conveys specific meanings in a particular context. Moreover, the Quran never repeats the full description of an event but only a particular section which is closely related to the theme of the second surah. In addition to describing this as a principle, Imam Biqai also presented numerous arguments for it in his commentary. The present article investigates these argument